2022
DOI: 10.3390/electronics11131956
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Total Nitrogen Content in Rubber Plantation Soil Based on Hyperspectral and Fractional Order Derivative

Abstract: Soil total nitrogen (TN) is a vital nutrient element that affects the growth and rubber production of rubber trees. Especially in the coastal environment, soil nutrients will show significant differences. Using hyperspectral technology to detect soil nitrogen ion content in the offshore environment can provide technical support for nutrient management. Preprocessing hyperspectral data is a crucial step in accurate spectral model estimation. At the same time, it is considered that the traditional first-order an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Performing (1/R), (LogR), ( √ R), and their first derivative transformations on the original spectral reflectance R can further reduce the noise effects caused by non-target factors such as lighting conditions, soil particle size, and air moisture in spectral measurements; highlight effective information in the spectrum; improve the sensitivity of characteristic bands [28]; and explore the optimal spectral transformation form [45]. CR, also known as envelope division, can effectively enhance the spectral characteristics of the region of interest [46][47][48].…”
Section: Collection and Preprocessing Of Hyperspectral Data On Tn In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Performing (1/R), (LogR), ( √ R), and their first derivative transformations on the original spectral reflectance R can further reduce the noise effects caused by non-target factors such as lighting conditions, soil particle size, and air moisture in spectral measurements; highlight effective information in the spectrum; improve the sensitivity of characteristic bands [28]; and explore the optimal spectral transformation form [45]. CR, also known as envelope division, can effectively enhance the spectral characteristics of the region of interest [46][47][48].…”
Section: Collection and Preprocessing Of Hyperspectral Data On Tn In ...mentioning
confidence: 99%
“…Niu et al constructed a hyperspectral estimation model for TN content in Shajiang black soil and found that the accuracy of the SVM model was slightly higher than that of the indices model, but both models could facilitate the rapid estimation of TN content in Shajiang black soil [24]. The spectral estimation technology of soil nutrients has achieved some preliminary results in the research in apple orchards [25,26], navel orange orchards [27], and rubber orchards [28]. Liu et al constructed an estimation model for soil organic matter content in apple orchards using the random forest method, and the R 2 of the modeling sample set reached 0.88 [29].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of modelling inversion, scholars have found that different models perform differently because of the differences in computational principles; hence, it is necessary to construct different models to compare the inversion effects to determine the best inversion model [23][24][25]. Owing to the redundancy of hyperspectral data, a mathematical transformation of spectral data or of the extraction of sensitive bands via principal component analysis and the correlation coefficient method can improve the modelling accuracy [26][27][28]. Naveen et al collected soil hyperspectral data from mangrove and salt marsh wetlands and established a partial least-squares regression model between the spectral information and soil carbon and nitrogen variables in an attempt to determine the best band for soil variable inversion [29].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2022) developed a model utilising RR, PLSR, support vector machine regression (SVR), and random forest (RF) to estimate nitrogen content in winter wheat leaves quantitatively. Tang et al (2022) investigated the optimal estimation model for soil total nitrogen using fractional order derivative (FOD) and found that this enhanced the model's estimation ability. Niu et al (2023) analysed the spectral data with various pretreatment methods and concluded that the accuracy of the soil total nitrogen content prediction model was influenced by the chosen preprocessing method.…”
mentioning
confidence: 99%